PECULIARITIES OF APPLICATION OF LONGITUDINAL DATA MODELS FOR AGRICULTURAL ENTERPRISES - Окселенко, Н. О. (Scientific Progress & Innovations, 2013)
The work is devoted to the improvement of the current assets of management of the agricultural enterprises using the longitudinal data models. The system of econometric ANCOVA-models for agricultural enterprises is developed. The economic interpretation of all characteristics of the connection is given and the possibilities of the models use in practice are showed. Significant proportion of current assets of agricultural enterprises constitute reserves, accounts receivable, current biological assets. It was proved that the problem of the effective current assets management is at the same time a problem of profit management.